EKSPERIMENTASI MODEL PEMBELAJARAN KOOPERATIF TIPE STUDENT TEAMS ACHIEVEMENT DIVISIONS MODIFIKASI PENEMUAN TERBIMBING TERHADAP PRESTASI BELAJAR MATEMATIKA DITINJAU DARI KEMAMPUAN VERBAL - Herlina, Herlina (LPPM Universitas Terbuka, 2015)
The purpose of this study was to compare the learning achievement using cooperative learning model Student Teams Achievement Divisions with cooperative learning model Student Teams Achievement Divisions modification of guided discovery in terms of verbal abality. Based on the results of the study concluded that (1) based on a model of learning, the mathematics achievement of students who use cooperative learning model Student Teams Achievement Divisions as good with mathematics achievement of students who use cooperative learning model Student Teams Achievement Divisions modifications guided discovery, both on students who have the high verbal skills, medium and low, (2) base on terms of verbal skills, mathematics achievement of students who have high verbal ability is better than mathematics achievement of students who have medium and low verbal ability, and mathematics achievement of students have medium verbal skillsbetter than mathematics achievement of students have the ability low verbal skills. Tujuan penelitian ini adalah untuk mengetahui perbandingan prestasi belajar yang menggunakan model pembelajaran kooperatif tipe Student Teams Achievement Divisions dengan model pembelajaran kooperatif tipe Student Teams Achievement Divisions modifikasi penemuan terbimbing ditinjau dari kemamuan verbal. Berdasarkan hasil penelitian disimpulkan bahwa (1) berdasarkan model pembelajaran, prestasi belajar matematika peserta didik yang menggunakan model pembelajaran kooperatif tipe Student Teams Achievement Divisions sama baiknya dengan prestasi belajar matematika peserta didik yang dikenai model pembelajaran kooperatif tipe Student Teams Achievement Divisions modifikasi penemuan terbimbing, baik pada peserta didik yang memiliki kemampuan verbal tinggi, sedang dan rendah, (2) ditinjau dari kemampuan verbal, peserta didik yang memiliki kemampuan verbal tinggi lebih baik daripada peserta didik yang memiliki kemampuan verbal sedang dan rendah, dan peserta didik yang memiliki kemampuan verbal sedang lebih baik daripada peserta didik yang memiliki kemampuan verbal rendah.